INOVASI SISTEM MANAJEMEN KINERJA SDM TERINTEGRASI DENGAN BIG DATA DI BPJS KESEHATAN - Riyadi, Muhammad Kadar (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2019)
In the era of globalization, innovation is one thing that many people talk about in order to try to create a form or thing or thing that can make an activity more effective and efficient. The challenge of continuing to innovate does not only come to humans individually but also extends to the scope of the organization. This study aims to see the dynamics that occur in the innovation process carried out by BPJS Kesehatan by taking a case study on the HR performance management sistem. Data was obtained through in-depth interviews with five research sources using a qualitative approach. The results showed that there are three main dimensions of the development process of HR performance management system innovation at BPJS Kesehatan, namely: forming a unified data from existing personnel sistems, building a system that can integrate modules for performance, talent and career, and build system development. The dimension of integrating performance modules, talents and careers into an integrated system is characteristic of this research when compared to other findings regarding the processes and stages of innovation. Innovation in the performance management system at BPJS Kesehatan is a tangible form that organizations see employees as talent and are key competitive assets and key factors for future organizational success.